Federal Taxation in America : - Brownlee, W. Elliot (Cambridge University Press, 2004)
Extending from the ratification of the Constitution to the present day. W. Elliott Brownlee describes the five principal stages of federal taxation in relation to the crises that led to their adoption--the formation of the republic, the Civil War, World War I, the Great Depression, and World War II. Now in a new edition, Brownlee expands his coverage to the present, with a new chapter focusing on the current tax policies of the Bush administration. This discussion is set within a larger analysis of contemporary tax and fiscal issues, including war finance, Social Security, and Medicare. First Edition Hb (1996): 0-521-56265-1 First Edition Pb (1996): 0-521-56586-3